Environmental Pollution and its Effects on Human Health - Gyawali, Kalpana; Acharya, Pitambar; Poudel, Deepak (Interdisciplinary Research in Education, 2023)
Environmental pollution poses a widespread issue with significant implications for the well-being of individuals and populations worldwide. The escalating utilization of fossil fuels, improper sewage disposal practices, and indiscriminate use of agricultural pesticides contribute to the pervasive presence of environmental pollution across the globe. To assess the state of environmental pollution and its impact on human health on a global scale, a comprehensive review of relevant scholarly articles was undertaken. The deleterious effects of pollution manifest in elevated rates of cancer, cardiovascular disease, respiratory ailments, mental disorders, and diarrhea. Each year, approximately 7 million individuals succumb to air pollution-related causes, while an additional 1.6 million people perish due to diseases stemming from water pollution. Environmental pollution emerges as a principal determinant of human morbidity and mortality worldwide, with low-income nations displaying heightened vulnerability. Given the escalating burden of pollution in the modern era, concerted and collaborative efforts by all relevant entities and nations are imperative to mitigate the extent and consequences of pollution on the global environment and human health.